INFLUENCE OF FERTIGATION LEVELS AND DRIP IRRIGATION LEVELS ON YIELDAND QUALITY OF RABI CHILLI UNDER MULCH AND NO MULCHED CONDITIONS - BABY AKULA and S.TRIVENI, RANI BATHULA, M. UMA DEVI, A. MADHAVI, K. AVIL KUMAR (The Journal of Research, PJTSAU, 2026)
The field investigation was carried out during rabi season to evaluate the influence of fertigation levels, mulching and drip irrigation levels on fresh fruit yield and yield quality at WTC fields, PJTSAU, Rajendranagar, Telangana in 2020-21 and 2021-22. The study was consisted of 12 treatment combinations viz.. 75 %, 100 % (300-60-120 kg ha-1 N-P2O5-K2O) & 125% RDF, drip irrigation levels (0.8 Epan & 1.0 Epan) imposed under factorial combination of mulch (M1) and no mulch (M0) conditions. Among the fertigation levels, 100% RDF (31.15 t ha-1, 195.04 mg 100 g-1, 10.33 % & 0.94 %, respectively) recorded the higher fresh fruit yield, ascorbic acid content, oleoresin content and capsaicin content in pooled data. Mulching treatment has recorded the higher values for fresh fruit yield (37.56 t ha-1), ascorbic acid content (224.43 mg 100 g-1), oleoresin content (11.11 %) and capsaicin content (0.74 %) in pooled data when compared to unmulched treatment.